Arginine methylation regulates Ewing sarcoma cell viability in a EWSR1::FLI1 dependent manner and provides a therapeutic opportunity - Ward, Ciara M.; Brockwell, Charles; McNee, Gavin S.; Orton, Emily; Prowse, Emily N. P.; Gatz, Susanne A.; Davies, Clare C. (Frontiers in Oncology, 2025)
IntroductionEwing sarcoma is a rare type of cancer arising from bone and soft tissues mainly affecting children and young adults. Treatments include intensive chemotherapy, surgery and radiotherapy, however more than 30% of patients die from the disease. Direct drug targeting of EWS-FLI1 remains a significant challenge, therefore new approaches are urgently required.MethodsAnalysis of PRMT1 and PRMT5 transcript expression using the R2 platform focusing on the Filion dataset of sarcomas that includes Ewing sarcoma patients alongside other fusion-positive sarcomas and breast and lung cancer datasets. Immunoblotting across a panel of Ewing sarcoma cell lines detected PRMT1 and PRMT5 expression and associated activity. Cell viability assay after PRMT inhibition, with and without olaparib, were conducted by trypan blue exclusion and MTT assay. DNA damage was detected by immunofluorescence staining for markers of DNA damage (γH2AX) and double-strand breaks (53BP1).ResultsWe show that the expression and activity of the arginine methyltransferases PRMT1 and PRMT5 are elevated in Ewing sarcoma and that inhibition of PRMT1 or PRMT5 with pre-clinical inhibitors leads to growth arrest and apoptosis that is dependent on the expression of the driver oncogene EWSR1::FLI1. Mechanically, we show that PRMT1 and PRMT5 inhibitors promote DNA damage, and that PRMT5 inhibitors synergise with the PARP inhibitor olaparib to induce elevated DNA damage and reduced cell viability.DiscussionOur study implies that PRMT1/PRMT5 are important mediators of EWSR1::FLI1 oncogenicity and that drug targeting PRMT1/PRMT5 in combination with DNA damaging chemotherapies could be an effective therapeutic strategy for the treatment of ES patients.